2007
DOI: 10.2193/2006-026
|View full text |Cite
|
Sign up to set email alerts
|

Off‐Highway Vehicle Trail Impacts on Breeding Songbirds in Northeastern California

Abstract: Rapid growth in off‐highway vehicle (OHV) use in North America leads to concerns about potential impacts on wildlife populations. We studied the relationship between distance to active OHV trail and songbird nesting success and abundance in northeastern California, USA, from 2002 to 2004. We found evidence of greater nest desertion and abandonment and reduced predation on shrub nests <100 m from OHV trails than at nests >100 m from OHV trails. Two of 18 species studied were less abundant at sites on trails tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…The USDA Forest Service has proposed to amend OHV regulations in an attempt to mitigate the environmental damage inflicted by these vehicles (USDA Forest Service, 2004). It has been demonstrated that OHV use reduces the abundance of bird species and increases the desertion rates of nests in Northeastern California (Barton and Holmes, 2007). In Algodones Dunes in California, a study showed that OHV usage reduces the density of a threatened plant by 4-5 times, and that plants struck by OHVs have survival rates reduced by 33% (Groom et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The USDA Forest Service has proposed to amend OHV regulations in an attempt to mitigate the environmental damage inflicted by these vehicles (USDA Forest Service, 2004). It has been demonstrated that OHV use reduces the abundance of bird species and increases the desertion rates of nests in Northeastern California (Barton and Holmes, 2007). In Algodones Dunes in California, a study showed that OHV usage reduces the density of a threatened plant by 4-5 times, and that plants struck by OHVs have survival rates reduced by 33% (Groom et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Arthropods, lizards, and mammals experienced marked declines in portions of sand dunes used by OHVs in southeastern California (Luckenbach and Bury ), and OHV activity in the Mojave Desert was associated with reduced densities and body mass of desert tortoises ( Gopherus agassizii; Bury and Luckenbach ). Breeding songbirds were less abundant, and nest abandonment rates higher near OHV trails in northeastern California (Barton and Holmes ). However, thus far, long‐term effects of OHV activity on populations of large avian predators have not been documented.…”
mentioning
confidence: 99%
“…Recreational OHV use in California's desert southwest is increasing in popularity, likely to the detriment of flora and fauna (Cordell, Betz, Green, & Mou, ). Off‐highway vehicle activity has been found to directly kill native plants and animals, alter animal movements, reduce reproductive and nesting success, compact soil, change water runoff patterns, and increase susceptibility to erosion (Barton & Holmes, ; Groom, McKinney, Ball, & Winchell, ; Lovich & Bainbridge, ). Given these negative impacts, restricting OHV use in areas projected to be of high conservation value in the future may be an important step towards minimizing conflicts between recreation interests and biodiversity conservation.…”
Section: Discussionmentioning
confidence: 99%